Mapping institutional arrangements for infrastructure governance in OECD countries - Ruiz Rivadeneira, Ana Maria (OECD Working Papers on Public Governance, 2023)
Multiple institutions are responsible for and contribute to ensuring that infrastructure investments meet policy objectives. The responsibilities of these institutions have evolved over time and vary from country to country, depending on tradition, constitutional arrangements, and government capacities. While they are often complementary, sometimes these responsibilities overlap, creating an additional level of complexity. Understanding the impact of the institutions involved with infrastructure will allow policymakers to make informed decisions. This paper explores both the 'why' and the 'what' of institutional arrangements. It provides a snapshot of the various institutions involved in the planning, financing, and delivery of infrastructure across OECD Member countries and identifies three broad types of institutional arrangements. The paper contributes to a better understanding of current trends in institutional change, the strengths and challenges of these institutional arrangements, and the potential for sharing experience and expertise among institutions and countries